Unattended pristine installation with IBM Tivoli Configuration Manager - Hochstetler, Stephen (IBM redbooks., 2003)
Pristine installations of operating systems is a strategic method to ensure that the security of your machines is maintained and that no one has left accounts or Trojan horses on your servers waiting to be executed at a later date. For this reason, reasonable methods to complete this task from a central location is necessary to reduce IT costs. Each vendor has produced software and methods for being able to roll out a new operating system in an unattended fashion. This IBM Redbooks publication ties each of those solutions into a centralized overall solution using IBM Tivoli Configuration Manager Version 4.2. It is important to understand that all the features and enhancements tie together to enable the environment more flexibility, efficiency, and faster deployment, helping to cut costs and time. Pristine installation of software is the first important step of managing your networked computers. IBM Tivoli Configuration Manager Version 4.2 provides an "attended" pristine installation using the Pristine tool. This book explores integrating IBM Tivoli Configuration Manager with tools that provide unattended pristine installations.